2022
DOI: 10.3390/fermentation8080410
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Lager—Brewing with Lutra® Kveik Yeast

Abstract: Brewers commonly produce ales since the ale yeast is more resilient, ferments quicker and requires higher temperatures, which are easier to ensure as opposed to lager and pilsner, which require lower temperatures and longer lagering time. However, Kveik yeasts are also resilient, ferment at fairly high temperatures (up to 35 °C), and can provide light, lager-like beers, but more quickly, in shorter lagering time, and with reduced off flavors. Diacetyl rest is not needed. The intention of this paper was to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Limited work has so far been carried out on the phenotypic diversity of farmhouse yeasts. Prior work on a relatively small subset of ‘kveik’ isolates has revealed that they tend to ferment wort rapidly, have high thermotolerance, and can produce beers ranging from clean and neutral to strongly aromatic (Preiss et al 2018; Foster et al 2022; Kawa-Rygielska et al 2022; Habschied et al 2022; Dippel et al 2022). Here, we reveal that farmhouse yeast, including kveik, show significant phenotypic diversity, both in regards to fermentation dynamics and flavour formation.…”
Section: Discussionmentioning
confidence: 99%
“…Limited work has so far been carried out on the phenotypic diversity of farmhouse yeasts. Prior work on a relatively small subset of ‘kveik’ isolates has revealed that they tend to ferment wort rapidly, have high thermotolerance, and can produce beers ranging from clean and neutral to strongly aromatic (Preiss et al 2018; Foster et al 2022; Kawa-Rygielska et al 2022; Habschied et al 2022; Dippel et al 2022). Here, we reveal that farmhouse yeast, including kveik, show significant phenotypic diversity, both in regards to fermentation dynamics and flavour formation.…”
Section: Discussionmentioning
confidence: 99%
“…K. Habschied et al (2022) evaluated the possibility of using Lutra® Kveik yeast for the production of pseudo-lager. The beer produced showed good physical and chemical quality indicators, comparable to ordinary light beer made using unmalted grain and enzyme preparations.…”
Section: Viscositymentioning
confidence: 99%